How Ben Franklin stole the lightning - Schanzer, Rosalyn (HarperCollins, 2003)
Focuses on Benjamin Franklin's role as an inventor of whimsical gadgets and practical contraptions, with an emphasis on his experiment of flying a kite during a rainstorm.